2019
DOI: 10.1590/1517-869220192503195048
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Training Load and Recovery in Volleyball Players During a Season

Abstract: Introduction Monitoring training loads, along with the recovery status, is important for preventing unwanted adaptations. Knowledge of these variables over volleyball seasons is still scarce. Objective To monitor and describe the training load and recovery status of volleyball players over a competitive season. Methods The sample consisted of 14 professional volleyball players. For the entire season, the training load was monitored daily by the SPE method during the session, and the recovery status was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 21 publications
0
29
0
1
Order By: Relevance
“…8,9 The reduced number of players and larger area to cover increase the individual stress level during training and competition compared to regular volleyball settings. 10,7 In order to monitor internal training response, different markers (session rate of perceived exertion [s-RPE], Delayed onset of muscle soreness [DOMS] and creatinkinase [CK]) were analyzed for indoor volleyball 8,11,12 but only one work evaluated elite beach volleyball players. 7 The authors identified different levels of s-RPE among blockers and defenders and between different mesocycles within a 10 week observation in a case study of 2 elite players.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The reduced number of players and larger area to cover increase the individual stress level during training and competition compared to regular volleyball settings. 10,7 In order to monitor internal training response, different markers (session rate of perceived exertion [s-RPE], Delayed onset of muscle soreness [DOMS] and creatinkinase [CK]) were analyzed for indoor volleyball 8,11,12 but only one work evaluated elite beach volleyball players. 7 The authors identified different levels of s-RPE among blockers and defenders and between different mesocycles within a 10 week observation in a case study of 2 elite players.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these variables showed predictive power over RPE-4 and S_RPE-4. Such findings show that higher internal intensities are correlated with lower external intensities in sessions further away from the game day, a fact not found on the days closest to the game, and it is possible to suggest that there is an oscillation in the training load during the week, allowing the athlete to recover throughout the sessions so that they are recovered on the game day [ 38 ]. Similar findings were found by Mendes et al [ 39 ] analyzing soccer athletes; these authors noticed that athlete fatigue, stress level, and internal intensity were significantly higher in the two training sessions immediately after match day.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of training highly qualified athletes, a relatively short general preparatory stage and a long special preparatory stage are usually planned. For athletes with low qualifications, the opposite ratio is reported [13,14].…”
Section: Original Articlementioning
confidence: 99%